Эффект Пигмалиона: всепобеждающая сила любви - Дубицкий, А. Е. (ХНУРЕ, 2020)
Love is a complex feeling that everyone experiences, without exception. extreme forms of expression of love: dominance and submission. A secret to a good relationship is the balance of these two notions. People often confuse the selfish need to be loved with a feeling of love, trying to force others fall in love with them, pressing on the victim, or on the other hand they, obediently serving to his or her “owner” giving everything away. One way or another, these are destructive games, the solution of which will be discussed in this article
Keywords: філософія; эффект Пигмалиона